INTEGRATING COMMUNITY-BASED PARTICIPATORY RESEARCH IN EDUCATIONAL STUDIES: A SOCIOLOGICAL FRAMEWORK FOR STAKEHOLDER ENGAGEMENT - Sumual, Tinneke Evie Meggy; Piri, Meiske Feiny Sialom; Tooy, Olivia Agustine; Onsu, Fadly Claudio; Toar, Stevanie F.; Toar, Rendy Christian; Tuerah, Paulus Robert (Labor Program Studi Pendidikan Sosiologi, 2022)
This study aims to examine the integration of Community-Based Participatory Research (CBPR) in educational studies through a sociological framework, focusing on stakeholder engagement and its implications for educational practice and policy development. The research employed a qualitative approach utilizing systematic literature review methodology, analyzing peer-reviewed articles published between 2015-2022 that focus on CBPR implementation in educational contexts and their sociological underpinnings. The findings reveal three key dimensions: (1) the transformation of power relations in educational research, demonstrating a shift towards more equitable collaboration between academic researchers and communities; (2) the crucial role of sociological frameworks in understanding community dynamics and their influence on educational outcomes; and (3) the sustainable impact on educational policy development through enhanced stakeholder engagement and evidence-based advocacy. The study highlights how the integration of sociological perspectives in CBPR can facilitate more effective stakeholder engagement and sustainable educational change. Recommendations include developing more culturally responsive research methodologies and establishing mechanisms for measuring the long-term impact of participatory approaches in educational research and policy development. These findings contribute to the growing body of knowledge on participatory research methods in education while providing practical insights for researchers, educators, and policymakers seeking to enhance community engagement in educational transformation.